Are religiosity and prayer use related with multiple behavioural risk factors for chronic diseases in European adults aged 50+ years?. Issue 5 (May 2015) - Linardakis, M.; Papadaki, A.; Smpokos, E.; Sarri, K.; Vozikaki, M.; Philalithis, A.
Abstract Objectives Behavioural risk factors for chronic diseases involve factors relating to lifestyle habits. This study examined the relationship of religious and spiritual beliefs with the adoption and presence of multiple behavioural risk factors (MBRFs) in European adults. Study design Cross-sectional study. Methods Data were used from 16, 557 individuals, aged 50+ years, participating in the Survey of Health, Ageing and Retirement in Europe (2004/05). MBRFs clustering was defined by high body weight, smoking, physical inactivity and risky alcohol consumption, and regression estimations with religiosity and prayer use were assessed based on sampling weights. Results In total, 79.4% of participants had received religious education, 33.4% had used prayer '≥1 time/day' and 53.3% had clustering of 2+ MBRFs. Lower prevalence of smoking was found in males (20.6% vs. 29.4%, P < 0.05), as well as in females (13.1% vs. 22.6%, P < 0.05), who prayed '≥1 time/day', compared to those who never prayed. Categorical regression analysis revealed that the presence of MBRFs was associated negatively with religious education (standardized beta = −0.048, P < 0.001) and positively with low frequency of prayer use (standardized beta = 0.056, P < 0.001). Conclusions Having received religious education and prayer use were related to the presence of fewer MBRFs in European adults aged 50+ years. These lifestyle factors should be assessed as potential determinants of MBRFs adoption when examining chronic disease development in multicultural populations.